1994
DOI: 10.1177/000331979404500301
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Studies of Cerebral Perfusion and Cognitive Testing Among Elderly Normal Volunteers and Patients with Ischemic Vascular Dementia and Alzheimer's Disease

Abstract: To compare longitudinal changes of cerebral perfusion (CBF) and cognitive status in two common forms of dementia in the elderly, 42 patients with ischemic vascular dementia (IVD), 44 patients with dementia of the Alzheimer type (DAT), and 120 elderly normal volunteers were evaluated prospectively over a mean interval of 3.35 years. Subjects were at least age sixty, (mean age 71.1). Mean bihemispheric cerebral blood flow and cognitive test scores of control subjects were significantly higher than those of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, this is even more likely in studies drawing longitudinal conclusions (changes of ageing) from crosssectional data (i.e. Meyer and collaborators [2,3,20] have performed large longitudinal studies on rCBF and ageing, avoiding these confounds. Meyer and collaborators [2,3,20] have performed large longitudinal studies on rCBF and ageing, avoiding these confounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is even more likely in studies drawing longitudinal conclusions (changes of ageing) from crosssectional data (i.e. Meyer and collaborators [2,3,20] have performed large longitudinal studies on rCBF and ageing, avoiding these confounds. Meyer and collaborators [2,3,20] have performed large longitudinal studies on rCBF and ageing, avoiding these confounds.…”
Section: Discussionmentioning
confidence: 99%
“…Cessation of smoking and lowering elevated cholesterol levels had been the main types of preventive treatments. [64][65][66][67][68][69] Studies have shown that control of hypertension and other stroke risk factors improved or stabilized cognitive function. 66,67 It is also well known that treating hypertension aggressively in the elderly with medications such as diuretics and betablockers, decreases the risk of stroke by as much as 25 percent or more.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has linked cognitive decline and dementia to CVD, 1 stroke, 2 diabetes mellitus (DM) and glucose metabolism, [2][3][4][5][6][7][8][9][10][11] hypertension and high and low blood pressure, 2,[12][13][14][15][16][17] peripheral vascular disease, 18 atherosclerosis, 19 genetic factors, 20,21 and cerebral blood flow. 22,23 Apolipoprotein E ⑀4 (APOE ⑀4) genotype is associated with an increased risk of dementia and cognitive decline. 24 Apolipoprotein E ⑀4 alleles may account for 13% to 20% of dementia cases.…”
Section: T He Influence Of Cardiovas-mentioning
confidence: 99%